Liver Nodules Crash Course - Andrew Arifin; David Driman; Jeremy Parfitt (Association of American Medical Colleges, 2016)
Abstract Introduction The Liver Nodules Crash Course is a web-based module that facilitates self-learning of the pathology of liver nodules, including histology and diagnostic approach. It builds on previous work of similar modules, including our previously published GI Biopsy Crash Course and Liver Biopsy Crash Course. Methods The module features interactive elements to demonstrate the histological features of each liver nodule, as well as review questions integrated into the module. It is particularly unique in that it simulates looking at real histopathology slides and allows a medical trainee with minimal prior histopathology exposure to rapidly develop basic proficiency in liver nodules pathology-enough to function in liver pathology rounds. The module can be distributed to each learner or hosted on a learning management system. We expect that the performance of students completing the module will improve significantly, although this has not been formally evaluated yet. Results The overall response of learners who have completed this module has been overwhelmingly positive. Representative comments include: "I wish I had these a couple years ago... I wish there were more such modules on other topics," and "These modules were really professional. The image quality is fantastic and the information is laid out very clearly. I learned some new things too." Discussion The Liver Nodules Crash Course builds on our previous work in developing interactive self-learning modules for basic gastrointestinal and liver pathology. All of the modules in the series have been effective teaching tools for gastroenterology/hepatology fellows participating in pathology rounds, off-service residents rotating through pathology, and junior-level pathology residents.